Back to the future : using marketing basics to provide customer value : proceedings of the 2017 Academy of Marketing Science (AMS) Annual Conference /: using marketing basics to provide customer value : proceedings of the 2017 Academy of Marketing Science (AMS) Annual Conference. (2017) - Unknown
No abstract available